Plant DNA barcoding and metabolomics for comprehensive discrimination of German Chamomile from its poisonous adulterants for food safety. (June 2022) - Mahgoub, Yasmin A.; Shawky, Eman; Eldakak, Moustafa; Bahey-El-Din, Mohammed; Darwish, Fikria A.; El Sebakhy, Nadia A.; El-Hawiet, Amr
Abstract: German Chamomile ( Matricaria recutita L.) is one of the most consumed herbal teas in the world. Deliberate and undeliberate adulteration in German Chamomile raw material represents serious concerns for consumers' safety. Authentication of Matricaria recutita L. samples was performed using an integrative approach of DNA barcoding and chemical profiling. Discrimination of M. recutita from three morphologically related species namely Anthemis cotula L., Senecio desfontainei Druce and Senecio vulgaris L. was accomplished. Three plastid loci (mat K, rbcL and psbA-trnH) and two nuclear spacers (ITS and ITS2) were utilized for the DNA barcoding of M. recutita . The Chemical profiling of M. recutita was achieved using untargeted HPTLC-image analysis. Among the tested barcoding loci, ITS2 revealed the maximum genetic diversity among the studied plants. ITS2 showed adequate polymorphic sites to detect interspecific variation with high amplification and sequencing success. Chemical profiling showed that flavonoids, coumarins, sesquiterpene lactones and phenolic acids are the main secondary metabolite classes of the candidate plants. While, flavonoids and phenolic acids served as quality markers, sesquiterpene lactone (anthecotulide) and pyrrolizidine alkaloid (senecionine) accounted as toxicity markers for the adulterants. Notably, coumarin accumulation pattern could be utilized to discriminate M. recutita from its adulterants due to the absence of hernarin and umbelliferone from Senecio species. The results of this study suggest that, integrating genetic and metabolomic fingerprinting could serve as an effective tool, with 100% success rate, in authenticating M. recutita and discriminating its samples from the morphologically related toxic adulterants. This offers a comprehensive tool for the quality control of M. recutita samples in food industry. Highlights: ITS2 could discriminate German chamomile from its toxic common adulterants. Coumarin accumulation could differentiate German chamomile from its adulterants. Flavonoids and phenolic acids serve as quality markers for German chamomile. Anthecotulide and senecionine represent toxicity markers for the adulterants.